Managing Dual Practice of Health Workers: Evidence from Indonesia - Paula Gonzalez; Gabriel V. Montes-Rojas; Sarmistha Pal (Institute of Labor Economics (IZA), 2021)
Managing dual practice of health workers has often proved to be challenging, especially in emerging countries characterized by weak monitoring and low motivation. This paper exploits an exogenous variation in the initiation of private practice among heads of local public facilities (known as puskesmas) providing primary health care after the introduction of a 1997 health regulation in Indonesia. This regulation required health professionals to apply for a license for private practice at least three years after their graduation. Exploiting the exogenous variation in private practice after the 1997 regulation, we provide estimates of causal effects of dual practice on provision of public health services, distinguishing between the effects when private practice is located at or away from the public hospital. The estimates suggest that dual practitioners (relative to those engaged in public service only) work significantly less hours per week while they see significantly more patients in their public facilities. These adverse effects of dual practice are most pronounced when private practice is held away from the puskesmas. These results have important bearings on human resource management of universal health care provision.
Keywords: I10; I18; J2; J44; J45; O1; 330; dual practice of health professionals; Indonesia; Ministry of Health regulation 916; weak monitoring; difference-in-differences